PEMANFAATAN PELAYANAN KESEHATAN OLEH PESERTA BPJS KESEHATAAN DI PUSKESMAS LIPAT KAJANG KECAMATAN SIMPANG KANAN KABUPATEN ACEH SINGKIL TAHUN 2021 - Sri Agustiani; Basri Aramico; Surna Lastri (Jurnal Real Riset, 2022)
This study aims to determine the utilization of health services by BPJS Kesehatan participants at the Fold Kajang Health Center in 2022. This study is an analytic study with a cross sectional design. This research was conducted at the Fold Kajang Health Center in 2022. The population of this study was the BPJS Health participants at the Fold Kajang health center totaling 7401 people. The sample in this study were 99 people. Data were analyzed using chi square test. The results of this study indicate that 36.8% who utilize health services, which are not optimally utilize as much as 10.5%. The results of the Chi-Square statistical test obtained the value of = 0.000. The results of the phi coefficient test obtained the value of = 0.072, this indicates that the relationship is strong in the category of weak relationship (0.01-0.25). It can be concluded that there is a relationship between the BPJS Participant factor and the utilization of Health Services at the Fold Kajang Health Center in 2022 (weak relationship). There is a relationship between BPJS health participants and the utilization of health services at the Fold Kajang Health Center. There is no relationship between the role of health workers on the utilization of health services at the Fold Kajang Health Center. There is no relationship between the attitude factors towards the utilization of health services at the Fold Kajang Health Center. There is a relationship between the factors of access to the utilization of health services at the Fold Kajang Health Center and there is a relationship between the knowledge factor on the utilization of health services at the Fold Kajang Health Center.Keywords: Utilization of Health Services, BPJS Health